The Persian Brief Illness Perception Questionnaire: Validation in Patients with Chronic Nonspecific Low Back Pain - Sarvenaz Karimi-Ghasemabad; Behnam Akhbari; Ahmad Saeedi; Saeed Talebian Moghaddam; Noureddin Nakhostin Ansari (The Scientific World Journal)
Background. Illness perceptions may influence coping behaviors as well as treatment and recovery among patients with chronic pain including low back pain (LBP). These perceptions may vary across different conditions. The Brief Illness Perception Questionnaire (BIPQ) is used as an instrument to assess the patients’ perception of illness. Although the BIPQ has been previously translated into Persian, its psychometric properties have not been evaluated among patients with chronic nonspecific LBP. The aim of this study was to determine the reliability and validity of the Persian BIPQ in patients with chronic nonspecific LBP. Methods. 116 patients with chronic nonspecific LBP with a mean (standard deviation) age of 36.4 years (10.7) participated in this cross-sectional study. Fifty patients were reexamined after 10 to 12 days for test-retest reliability. Internal consistency reliability, construct validity, concurrent criterion validity, and structural validity were evaluated. The concurrent validity was examined by using the Short Form-36 Health Survey. Results. There were no floor and ceiling effects. Cronbach’s alpha for the total score was 0.90. The intraclass correlation coefficient (ICC) for test-retest reliability was 0.90. The standard error of measurement and the minimal detectable change was found to be 3.26 and 9.04, respectively. The convergent correlations confirmed the construct validity. The concurrent criterion validity was demonstrated by significant negative correlations with the SF-36. The Exploratory Factor Analysis produced the 2 factors (emotional illness representations and cognitive illness representations) with an eigenvalue >1.0 that jointly accounted for 58.86% of the total variance. Conclusion. The Persian BIPQ is a reliable and 2-factor instrument and can be used for assessing illness perception in patients with chronic nonspecific LBP.